The Effectiveness of the Blended Learning Model to Increase the Learning Motivation of Primary School Students - Afrida Hanum; Nena Puspita Sari (International Conference on Multidisciplinary Research, 2022)
This study aimed to examine the effectiveness of blended learning on students' learning motivation at primary schools. The method used was descriptive research with a qualitative approach. The study was carried out by observing the blended learning process in the class without making changes to the observed class. The population in this study was all fourth graders, totaling 61 students. The research samples were all students of Class IVA, totaling 30 students. Blended learning was employed in this class. Questionnaires were distributed to the students who participated in blended learning to collect the research data. There were four indicators in the motivation questionnaire, namely persistence, tenacity in the face of difficulties, interest in learning, and confidence. The data from the questionnaires were then analyzed using a Likert scale. The results by the average indicator show that the student learning motivation is 94, which belongs to a very high category. The average value of each indicator is the persistence indicator scoring 97; the tenacity indicator in the face of difficulties is 90; the interest in learning indicator is 96; and the confidence indicator is 95. The results of the overall questionnaire analysis belong to the high category. Thus, it can be concluded that blended learning is effective in increasing the students' learning motivation at SDN 1 Lambheu, District of Aceh Besar. As blended learning provides opportunities for students to learn independently, the students can study anywhere and broaden their horizons by accessing the learning resources globally. Keywords: Blended Learning, Motivation, Primary School